2017
DOI: 10.4049/jimmunol.1700792
|View full text |Cite
|
Sign up to set email alerts
|

NFM Cross-Reactivity to MOG Does Not Expand a Critical Threshold Level of High-Affinity T Cells Necessary for Onset of Demyelinating Disease

Abstract: Of interest to the etiology of demyelinating autoimmune disease is the potential to aberrantly activate CD4+ T cells due to cross-recognition of multiple self-epitopes such as has been suggested for MOG35-55 and NFM15-35. NFM15-35 is immunogenic in C57BL/6 mice but fails to induce demyelinating disease by polyclonal T cells despite having the same TCR contact residues as MOG35-55, a known encephalitogenic antigen. Despite reported cross-reactivity with MOG specific T cells, the polyclonal response to NFM15-35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…To test whether low-efficiency TCR ligands are optimal for induction of Tregs, we devised an alternative experimental system based on the observation that the 2D2 TCR recognizes two distinct NAg, including MOG35-55 as a low affinity antigen and NFM13-37 as a high affinity antigen (60, 61). We derived an expression system for GMCSF-NFM, which exhibited GM-CSF activity equivalent to that of GMCSF-MOG, GMCSF-OVA and GM-CSF in bone marrow proliferation assays (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether low-efficiency TCR ligands are optimal for induction of Tregs, we devised an alternative experimental system based on the observation that the 2D2 TCR recognizes two distinct NAg, including MOG35-55 as a low affinity antigen and NFM13-37 as a high affinity antigen (60, 61). We derived an expression system for GMCSF-NFM, which exhibited GM-CSF activity equivalent to that of GMCSF-MOG, GMCSF-OVA and GM-CSF in bone marrow proliferation assays (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…The low affinity nature of myelin peptides may reflect generalized mechanisms of self-tolerance, whereby high-affinity self-reactive clones are deleted during maturation and only low-affinity self-reactive clones persist in the periphery. Although high-affinity NFM13-37 peptide may represent an exception in regard to the specific 2D2 clonotype, the overall NFM-reactive repertoire may primarily comprise low-affinity clones because NFM13-37 lacks encephalitogenic activity in C57BL/6 mice (60).…”
Section: Discussionmentioning
confidence: 99%
“…When binding occurs between the two opposing cells an adhesion frequency is calculated [68]. T cells are additionally probed with RBCs coated with antigen-irrelevant pMHC monomers (Figure 2b) and those devoid of pMHC (Figure 2c) to determine any rates of non-specific binding [63,[69][70][71]. In the case of CD4+ T cells this control is often Class II invariant chain peptide (CLIP) as it is provided by the NIH tetramer core facility as the control for MHC class II tetramers due to the property that it binds to most MHC class II alleles.…”
Section: Specificity With High Sensitivity By 2d-micropipettementioning
confidence: 99%
“…Data from the 2D-micropipette assay in a variety of systems have revealed that lower affinity cells not only expand, but can also dominate polyclonal T cell expansion in the majority of systems tested [63,69,70,81,82,[84][85][86][87]. Thus, it is pertinent to consider the functional ramifications for a T cell that becomes activated via a lower affinity TCR.…”
Section: The Affinity Of Tcr For Pmhc Modulates Tcr-derived Signalsmentioning
confidence: 99%